Influence of Intermediaries on the Efficiency of Export of Small and Medium Business Production in Developing Countries - Suvaryan, Arzik Miqael; Mkrtichyan, Narina Grigorii; Manukyan, Hasmik Khachik (Economy of Regions, 2018)
Small and medium business plays an important role in the national economies of developing countries. From this perspective, to create an effective system for exports is of key importance for these countries. The article provides the basis for the implementation of intermediary export organizations and systems for their interaction with small and medium business entities. On the example of Armenia, the authors proved that the introduction of intermediary organizations to enhance the participation of small and medium business in export operations is expedient. These organizations may be implemented in other developing countries. We used methods of analysis, synthesis, induction, deduction, comparative method, statistical analysis and others. The authors proposed three possible options for establishing intermediary export organizations in developing countries.. Firstly, we considered the intermediary export organizations, established and managed directly by the state. Secondly, intermediary export organizations may be created by uniting of small and medium enterprises (SMEs) of a particular industry in association. And the final option is the commercial intermediary organizations for export. By applying a comparative cost analysis of direct and indirect exports, the authors have developed a method for assessing the effectiveness of interaction of intermediary export organizations with small and medium-sized businesses. We defined the following components of the total exports costs: the costs of warehousing, packaging, transportation, information collection, contracts, search for the shadow broker and interaction with him/her, marketing, export documentation, broker services, banking and insurance services, personnel costs, operation of the structure, tax and customs payments. We have analysed possible changes in these costs and defined the value of the cost changes total indicator that shows more effective indirect exports.. The study defines the possible risks faced by the exporter when entering the foreign market. These are the risk of interaction with unscrupulous buyers, the risk associated with the application of penalties and the inability to quickly ship the exported goods, and the long waiting times for loaded wagons. The research results can be applied to the implement or improve state policy in the sphere of small and medium enterprises, to develop medium- and long-term plans to optimize the activities of small and medium enterprises and their export strategy.